Adapting to an English-Dominated Academia: Challenges, Strategies, and Institutional Gaps Among Turkish Scholars - Selvi, Batuhan; Aldım, Umit Ferit (My University, 2026)
English-language publishing continues to present significant challenges for non-native English-speaking scholars, particularly those from underrepresented regions such as Turkey. This qualitative study explores the experiences of Turkish academics in publishing research articles in English, focusing on the linguistic, structural, and institutional barriers they encounter. Using a phenomenological research design, semi-structured interviews were conducted with 20 scholars across various disciplines. Thematic analysis revealed key challenges including language-related difficulties, the financial burden of translation and proofreading services, and perceived bias in peer review—often prioritizing linguistic accuracy over content quality. Participants reported relying on informal peer networks, AI- assisted writing tools, and professional editing services to meet international publishing standards. However, these solutions were often insufficient or financially inaccessible, highlighting deeper systemic inequities. The study also found inadequate institutional support for academic writing development, leaving scholars to navigate the publication process independently. These findings underscore the need for systemic reforms in academic publishing—namely, greater institutional support, inclusive editorial practices, and recognition of linguistic diversity. Addressing these gaps is essential for building a more equitable publishing landscape where research is evaluated on scholarly merit rather than linguistic proficiency.
Keywords: Academic publishing; Turkish scholars; institutional support; publishing inequalities; English-medium journals